Role of Cationic and Anionic Dopants on the Structural, Morphological, Optical and Magnetic Properties of Lead Oxide Nanocrystals Prepared by Solvothermal Method - Saraswathi, N.; Abhirama, K.J. (Asian Journal of Chemistry, 2021)
A facile and simple microwave assisted solvothermal technique was adopted for the synthesis of undoped and doped (Mn2+, S2–) lead oxide nanoparticles. Thermogravimetric analysis and differential thermal analysis were carried out to realize the thermal behaviour of PbO nanoparticles. The synthesized nanoparticles were annealed at about 400 ºC. The calcined samples were characterized by powder X-ray diffraction, SEM, EDX, UV spectroscopic analysis and VSM measurement. The diffraction patterns of the prepared nanoparticles showed the formation of an orthorhombic phase of lead oxide. All the samples were in nano- regime with an average grain size of 22-26 nm. Spherical morphology of the samples was revealed in the SEM micrographs. EDX pattern confirmed the presence of cationic and anionic dopants. The band gap energy values range from 4.2 to 5.6 eV. The VSM measurement revealed that the sample has weak ferromagnetic nature.